Comparison of the antimicrobial activity of Ulmo honey from Chile and Manuka honey against methicillin-resistant Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. - Sherlock Orla; Dolan Anthony; Athman Rahma; Power Alice; Gethin Georgina; Cowman Seamus; Humphreys Hilary (BMC, 2010)
Abstract Background Honey has previously been shown to have wound healing and antimicrobial properties, but this is dependent on the type of honey, geographical location and flower from which the final product is derived. We tested the antimicrobial activity of a Chilean honey made by Apis mellifera (honeybee) originating from the Ulmo tree (Eucryphia cordifolia), against selected strains of bacteria. Methods Ulmo 90 honey was compared with manuka UMF® 25+ (Comvita®) honey and a laboratory synthesised (artificial) honey. An agar well diffusion assay and a 96 well minimum inhibitory concentration (MIC) spectrophotometric-based assay were used to assess antimicrobial activity against five strains of methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli and Pseudomonas aeruginosa. Results Initial screening with the agar diffusion assay demonstrated that Ulmo 90 honey had greater antibacterial activity against all MRSA isolates tested than manuka honey and similar activity against E. coli and P. aeruginosa. The MIC assay, showed that a lower MIC was observed with Ulmo 90 honey (3.1% - 6.3% v/v) than with manuka honey (12.5% v/v) for all five MRSA isolates. For the E. coli and Pseudomonas strains equivalent MICs were observed (12.5% v/v). The MIC for artificial honey was 50% v/v. The minimum bactericidal concentration for all isolates tested for Ulmo 90 honey was identical to the MIC. Unlike manuka honey, Ulmo 90 honey activity is largely due to hydrogen peroxide production. Conclusions Due to its high antimicrobial activity, Ulmo 90 may warrant further investigation as a possible alternative therapy for wound healing.